Young Adults Living with Their Parents and the Influence of Peers - Effrosyni Adamopoulou; Ezgi Kaya (Institute for the Study of Labor (IZA), 2016)
This paper studies the impact of peer behavior on living arrangements of young adults in the U.S. Using data from the National Longitudinal Study of Adolescent Health (Add Health) we analyze the influence of high school friends on the nest-leaving decision of young adults. We achieve identification by exploiting the differences in the timing of leaving the parental home among peers, the individual-specific nature of the peer groups that are based on friendship nominations, and by including school (network) and grade (cohort) fixed effects. Our results indicate that there are statistically significant peer effects on the decision of young adults to leave parental home. This is true even after we control for labor and housing market conditions and for a comprehensive list of individual and family-of-origin characteristics that are usually unobserved by the econometrician. We discuss various mechanisms and we confirm the robustness of our results through a placebo exercise. Our findings reconcile with the increasing fraction of young adults living with their parents that is persisting in the U.S. even after the end of the Great Recession.
Keywords: D10; J12; J60; Z13; 330; peer effects; friends; living arrangements; leaving parental home